(untitled) (Mustansiria Dental Journal, 2024)
Materials and Methods: The present study included 2165 patients (2500 teeth were extracted) attending Oral Surgery clinic of the teaching hospital at College of Dentistry/ Mustansiriyah University during the period from October 2016 to May 2017. The patients’ ages ranged between (15-77 years). A standard case sheet for Oral Surgery clinic was filled with all the necessary information such as age, gender, tooth to be extracted and reasons of tooth extraction. Results: Dental caries and its complications were the primary cause of teeth extraction with (80.3%) followed by periodontal diseases (13.4) and other causes (6.4%). Tooth extraction due to dental caries was higher in males (59.2%) than females (40.8%). Tooth extraction due to periodontal diseases was also high in males (72.2%) compared to females (27.8%) with high significance (p= 0.000). In age groups 30-39 years and 40-49years, extraction due to dental caries was found equally high being 22.4%, while extraction due to periodontal diseases was high in age group ≥60 (38.3%) and in age group 50-59 (32.6%) with high significance (p = 0.000). Extraction of maxillary posterior teeth constituted (44.9%) and mandibular posterior teeth (37.8%), the posterior teeth were the most common teeth extracted because of caries, while mandibular anterior teeth (27.5%) followed by maxillary posterior teeth (26.6%) were the most common teeth extracted due to periodontal diseases with high significance (p = 0.000). Conclusion: Dental caries was the primary cause for tooth extraction followed by periodontal diseases. There was a significant correlation between the reasons for tooth extraction and the patient’s gender, age and tooth position. The study showed the need for a comprehensive preventive plans and effective educational campaigns to reduce the need for tooth extraction among adults and increase patient’s awareness toward better oral health status.